E-Course as Blended Learning Digital Educational Resource in University - Sorokova, M.G. (Psihologičeskaâ nauka i obrazovanie, 2020)
The article presents findings of the pilot empirical research on the performance of the ‘Mathematical Methods in Psychology’ e-course as an open digital educational resource for the implementation of blended learning using the ‘flipped classroom’ model at the university. The students' attitudes toward blended learning in the e-course format, their self-esteem of involvement in the learning process, as well as the educational results were examined. The main benefits for the students are the following: the accessibility of tutorials and information about their individual learning trajectory at any time; the convenience of self-preparation for classes. The students characterize the activity at seminars as active interaction with classmates and a teacher and involvement in the learning process. In general, the students positively assessed the use of digital resources in the blended learning educational process as a modern approach and expressed their wish to study other subjects or courses in this format (at other universities in Russia and abroad as well). No essential difficulties in taking the e-course were revealed. There is a correlation between the students’ positive evaluations of their own educational outcomes and their positive attitude to the new format (р < 0,001). The educational outcomes of the students after passing the e-course statistically significantly improved (р < 0,001). The blended learning group educational results are significantly higher as compared to traditional in-class education group (р < 0,001). The study was conducted at the Moscow State University of Psychology and Education. The total sample size N = 387 students of psychology departments, the experimental group size N = 78. The comparison group of traditional full-time education students (N = 309) is balanced with the experimental group in the following context parameters: gender and age, major academic disciplines, same teacher, MSUPE students. Представлены результаты пилотного эмпирического исследования возможностей электронного учебного курса «Математические методы в психологии» как цифрового образовательного ресурса смешанного обучения по модели «перевернутый класс» в МГППУ. Изучались отношение студентов к смешанному обучению в формате электронного курса, их самооценка вовлеченности в учебный процесс и образовательные результаты. Общий объем выборки составил 387 студентов психологических факультетов, экспериментальная группа — 78 человек, группа сравнения — 309 студентов традиционно-очного обучения, уравновешенная с экспериментальной группой по контекстным параметрам (половозрастной состав, направления и специальности подготовки, обучение у одного и того же преподавателя, принадлежность к МГППУ). Установлено, что основными преимуществами студенты считают доступность учебных материалов и информации о своей индивидуальной траектории прохождения курса в любое время, удобство при самостоятельной подготовке к занятиям. Деятельность на семинарах характеризуется ими как активное взаимодействие с однокурсниками и с преподавателем и вовлеченность в учебный процесс. В целом студенты положительно оценили использование электронного курса в образовательном процессе для смешанной формы обучения как современный подход и высказали желание изучать в этом формате и другие предметы, а также курсы в других университетах России и за рубежом. Существенных трудностей в изучении электронного курса выявлено не было. Подтверждена достоверная связь между положительной оценкой студентами своих образовательных достижений и их позитивным отношением к новому формату (р<0,001). Образовательные результаты студентов после прохождения электронного курса статистически значимо улучшились (р<0,001). Результаты студентов в группе смешанного обучения в формате электронного курса на выходе в среднем достоверно выше, чем в группе традиционно-очного обучения (р<0,001). Входного среза в группе традиционно-очного обучения проведено не было, однако по контекстным параметрам она полностью аналогична экспериментальной группе, поэтому нет никаких оснований предполагать различия знаний на входе. Исследование проведено в Московском государственном психолого-педагогическом университете.